2006
DOI: 10.1519/r-16674.1
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Body-Vibration–Induced Increase in Leg Muscle Activity During Different Squat Exercises

Abstract: ABSTRACT. Roelants, M., S.M.P. Verschueren, C. Delecluse, O. Levin, and V. Stijnen. Whole-body-vibration-induced increase in leg muscle activity during different squat exercises. J. Strength Cond. Res. 20(1):124-129. 2006.-This study analyzed leg muscle activity during whole-body vibration (WBV) training. Subjects performed standard unloaded isometric exercises on a vibrating platform (Power Plate): high squat (HS), low squat (LS), and 1-legged squat (OL). Muscle activity of the rectus femoris, vastus laterali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
123
2
8

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 139 publications
(142 citation statements)
references
References 25 publications
9
123
2
8
Order By: Relevance
“…WBV could increase VO 2 in part by inducing increased postural control (Abercromby et al 2007) but at least some of the increased VO 2 during the WBV exercise session is due to the increased exercise intensity resulting from the WBV-induced increase in skeletal muscle activity (Abercromby et al 2007;Cardinale and Lim 2003;Hazell et al 2007Hazell et al , 2010Marin et al 2009;Ritzmann et al 2010;Roelants et al 2006). Our data demonstrating a greater VO 2 and HR during the WBV exercise session compared to NoV are consistent with this suggestion.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…WBV could increase VO 2 in part by inducing increased postural control (Abercromby et al 2007) but at least some of the increased VO 2 during the WBV exercise session is due to the increased exercise intensity resulting from the WBV-induced increase in skeletal muscle activity (Abercromby et al 2007;Cardinale and Lim 2003;Hazell et al 2007Hazell et al , 2010Marin et al 2009;Ritzmann et al 2010;Roelants et al 2006). Our data demonstrating a greater VO 2 and HR during the WBV exercise session compared to NoV are consistent with this suggestion.…”
Section: Discussionsupporting
confidence: 81%
“…Regardless of the mechanism responsible, acute WBV exercise (both synchronous and side-alternating) has been shown to increase muscle activity, blood flow, and muscle/ skin temperature (Abercromby et al 2007;Cardinale and Lim 2003;Cochrane et al 2008;Hazell et al 2007Hazell et al , 2008Hazell et al , 2010Marin et al 2009;Ritzmann et al 2010;Roelants et al 2006) and has even been reported to increase strength, power, and performance (Bosco et al 1999;Cormie et al 2006; Da Silva-Grigoletto et al 2009;McBride et al 2010;Ronnestad 2009;Torvinen et al 2002a). However, there are also data showing little effect (de Ruiter et al 2003;Erskine et al 2007;Guggenheimer et al 2009;Torvinen et al 2002b) perhaps indicating that a wide range of exercise intensities are possible with WBV exercise.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, WBV did not increase HR or MAP versus that observed with the non-WBV semi-squat. Although previously, we and others have shown WBV increases in EMG activity versus the same exercise without the WBV stimulus (Cardinale and Lim 2003;Hazell et al 2007;Roelants et al 2006) the present findings indicate that superimposing WBV to a semi-squat exercise session produces minimal additional cardiovascular stress. The seated condition of this study was included to evaluate the effect of a WBV stimulus on inactive muscles not under tension (unloaded) because previous research has suggested that muscles and joints under tension have an increased response to the WBV perturbation (Hagbarth and Eklund 1966;Martin and Park 1997;Mester et al 1999;Nordin and Hagbarth 1996).…”
Section: Discussioncontrasting
confidence: 67%
“…Previous studies have suggested that WBV exposure results in increases in oxygen consumption [4.5 mL/ (kg min)] (Rittweger et al 2001), energy expenditure (Garatachea et al 2007), and EMG activity (Cardinale and Lim 2003;Hazell et al 2007;Roelants et al 2006). Our current data indicate intermittent semi-squat exercise with WBV when repeated for 15 repetitions (1 min on and 1 min off) increases common FBF and distal LSk temp minimally relative to the same exercise without vibration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation